Direct-Patterning ZnO Deposition by Atomic-Layer Additive Manufacturing Using a Safe and Economical Precursor - Stefanovic, Sonja; Gheshlaghi, Negar; Zanders, David; Kundrata, Ivan; Zhao, Baolin; Barr, Maissa; Halik, Marcus; Devi, Anjana; Bachmann, Julien (Small, 2023)
Area-selective atomic layer deposition (AS-ALD) is a bottom-up nanofabrication method delivering single atoms from a molecular precursor. AS-ALD enables self-aligned fabrication and outperforms lithography in terms of cost, resistance, and equipment prerequisites, but it requires pre-patterned substrates and is limited by insufficient selectivity and finite choice of substrates. These challenges are circumvented by direct patterning with atomic-layer additive manufacturing (ALAM) — a transfer of 3D-printing principles to atomic-layer manufacturing where a precursor supply nozzle enables direct patterning instead of blanket coating. The reduced precursor vapor consumption in ALAM as compared with ALD calls for the use of less volatile precursors by replacing diethylzinc used traditionally in ALD with bis(dimethylaminopropyl)zinc, Zn(DMP)2. The behavior of this novel ZnO ALAM process follows that of the corresponding ALD in terms of deposit quality and growth characteristics. The temperature window for self-limiting growth of stoichiometric, crystalline material is 200–250 °C. The growth rates are 0.9 Å per cycle in ALD (determined by spectroscopic ellipsometry) and 1.1 Å per pass in ALAM (imaging ellipsometry). The preferential crystal orientation increases with temperature, while energy-dispersive X-ray spectroscopic and XPS show that only intermediate temperatures deliver stoichiometric ZnO. A functional thin-film transistor is created from an ALAM-deposited ZnO line and characterized.
CRIS-Team Scopus Importer:2023-05-19
Keywords: additive manufacturing; atomic layer deposition; nanofabrication; sensors; zinc oxide